Persian Gulf 2023 - Quamar, Md. Muddassir. author. (orcid)0000-0003-1344-9643 Link aut Link
XXV, 459 p. 29 illus.
Keywords: The book is 10th in the Persian Gulf Series by Middle East Institute, New Delhi (MEI@ND) and 5th with Springer Nature. It focuses on regional developments in the Gulf and India’s relations with the region in the preceding years; hence, Persian Gulf 2023 focuses on events in 2022. The broad subject of the book is Indian foreign policy and international relations. The book is based on opensource data, statistics, and information including government and international organisations’ reports, reports published by important consultancy and research institutions focused on the Gulf region, news and media reports published in the Gulf region and India and should be of great interest to analysts, academics, journalists, students, and practitioners. Each chapter in the book has several tables and figures on economic indicators, bilateral trade, and energy-related developments. It is a reference work for anyone interested in the Gulf region and at the same time it offers valuable policy recommendations. Hence, it has both academic and policy relevance. Md. Muddassir Quamar is Associate Professor in Middle Eastern Studies at Jawaharlal Nehru University (JNU), New Delhi. Sameena Hameed is Associate Professor in Middle Eastern Studies at Jawaharlal Nehru University (JNU), New Delhi. P. R. Kumaraswamy is a Professor of contemporary Middle East at Jawaharlal Nehru University (JNU), New Delhi.